Riding the merger wave: Uncertainty, reduced monitoring, and bad acquisitions - Duchin, Ran; Schmidt, Breno (Journal of Financial Economics, 2013)
We show that acquisitions initiated during periods of high merger activity (“merger waves”) are accompanied by poorer quality of analysts' forecasts, greater uncertainty, and weaker CEO turnover-performance sensitivity. These conditions imply reduced monitoring and lower penalties for initiating inefficient mergers. Therefore, merger waves may foster agency-driven behavior, which, along with managerial herding, could lead to worse mergers. Consistent with this hypothesis, we find that the average long-term performance of acquisitions initiated during merger waves is significantly worse. We also find that corporate governance of in-wave acquirers is weaker, suggesting that agency problems may be present in merger wave acquisitions.